Sarong Bima: Elegance and Culture in Typical Cloth of West Nusa Tenggara - Sholehah, Wirda Zuriatun; Rosmianti, Rosmianti; Wirawan, Datu Arya; Sari, Ni Kadek Wahyuni Merta; Al Farisi, Moh Salam (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The industrial sector is one of the economic drivers in a region. Meanwhile, the industrial sector development in Bima Region is still poorly managed, especially the center of the Tembe Nggoli weaving industry. Therefore, there is a need for efforts by the NTB provincial government to properly manage it. Local economic development which can be done for the product is by using the industrialization concept. Thus, the purpose of writing this article is to examine the industrialization concept by the NTB provincial government as an effort to develop the local economy. The results showed that industrialization efforts by the NTB provincial government included trainings which are based on skills affirmation, business management, production equipment assistance, capital assistance, and even the value of packaging and marketing coverage workshop. The outcome of the training is to provide an expansion of employment opportunities, increase the quality and production capacity. This article used a literature approach, by examining several journals, books, electronic printed documents, and information relevant to the study. The discussion of the article is divided into several parts, 1) Characteristics of the typical woven pattern of Bima Tembe Nggoli; 2) Industrialization as an effort to develop the local economy; 3) Discussion; and 4) Conclusion.